2019
DOI: 10.3389/fmed.2019.00112
|View full text |Cite
|
Sign up to set email alerts
|

Association of Vitamin D Levels With Kidney Volume in Autosomal Dominant Polycystic Kidney Disease (ADPKD)

Abstract: Vitamin D possesses renoprotective effects beyond mineral metabolism, potentially reducing arterial blood pressure and inflammation and vitamin D enzymes (CYP24A1 and CYP27B1) as well as vitamin D receptor (VDR) contribute to its homeostasis. In the present study, we aimed to determine vitamin D association with kidney volume, blood pressure parameters and inflammatory markers in ADPKD. This cross-sectional study, conducted from August 2011 through May 2016, evaluated 25(OH)D, 1,25(OH)2D and other hormonal/bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 52 publications
(60 reference statements)
0
6
1
Order By: Relevance
“…In LPK rats, chronic dietary deficiency of vitamin D exacerbated proteinuria but unexpectedly caused a small but significant reduction in kidney cyst growth [19]. In contrast, in a small longitudinal cohort study of humans with ADPKD, low levels of 25-OH vitamin D did not predict changes in total kidney volume or blood pressure [36]. An important disease-specific finding of the current study was that neither early nor delayed treatment with paricalcitol altered kidney cyst growth [19].…”
Section: Discussioncontrasting
confidence: 65%
“…In LPK rats, chronic dietary deficiency of vitamin D exacerbated proteinuria but unexpectedly caused a small but significant reduction in kidney cyst growth [19]. In contrast, in a small longitudinal cohort study of humans with ADPKD, low levels of 25-OH vitamin D did not predict changes in total kidney volume or blood pressure [36]. An important disease-specific finding of the current study was that neither early nor delayed treatment with paricalcitol altered kidney cyst growth [19].…”
Section: Discussioncontrasting
confidence: 65%
“…However, very little is known about vitamin D levels as a predictor of progression in ADPKD. A recent, small, cross-sectional study observed no independent association of either 1,25(OH) 2 D and 25(OH)D levels with total kidney volume (28). In Lewis PKD rats (a hypertensive rodent model of PKD which phenotypically resembles ARPKD but is a genetic ortholog of human nephrocystin protein 9), chronic vitamin D deficiency had adverse effects on proteinuria, inflammation, cardiovascular health, and renal function, despite mild inhibitory effects on kidney enlargement (29).…”
Section: Discussionmentioning
confidence: 89%
“…The mechanisms of the newly introduced crucial genes such as PPIE remain to be identified with experimental studies. We pointed out TFs such as HNF4A, STAT3, VDR, TP53, and HIF1A associated with ADPKD [22,23]. In addition, other TFs as CLOCK in ADPKD pathogenesis firstly are described in this study.…”
Section: Discussionmentioning
confidence: 81%
“…Previous studies reported the association of ADPKD with some of TFs e.g. HNF4A, STAT3, VDR, TP53, and HIF1A [6, 20, 22, 23]. Also, the role of miR‐17 family and miR‐192 in cyst enlargement were identified [24,25].…”
Section: Resultsmentioning
confidence: 99%